Advancement of a smart fibrous capillary irrigation management system with an Internet of Things integration - Muhammad Khairie Idham Abd Rahman; Mohamad Shukri Zainal Abidin; Mohd Saiful Azimi Mahmud; Salinda Buyamin; Mohamad Hafis Izran Ishak; Abioye Abiodun Emmanuel (Bulletin of Electrical Engineering and Informatics, 2019)
This paper presents the development work for integrating an Internet of Things (IoT) with a fibrous capillary irrigation system based on the climatic demand estimated by the weather condition. The monitoring and control using an IoT system is critical for such application that is targeted for precision irrigation. The fibrous capillary irrigation system is managed by manipulating a water supply depth using the potential evapotranspiration (ETo). A soil mositure sensor was used to monitor the progress of the root water uptake and input the fuzzy logic system, to determine the water requirements for the crop medium. Experiment was conducted by using a Choy sum plant as the test crop grown in a greenhouse. The monitoring of the demand and management of the watering system was successful. The ETo data was able to approximate the crop water requirement in near real time.